Drivers of change in fragile environments: challenges to governance in Indian wetlands - Narayanan, N.C.; Venot, Jean-Philippe (2009)
In densely populated coastal wetlands with rich biodiversity, multiple, but generally competing, economic activities are common. This paper adopts a polycentric perspective to the study of wetlands management in India to assess the scope for sustainable and equitable use of these remarkable and threatened ecosystems. The analytical framework proves to be useful and highlights that the intertwined processes of environmental and social changes result from, and shape, governance patterns. The three wetlands studied share commonalities in their trajectories: high population pressure, the enclosure of the commons and subsequent capitalization of resources and social marginalization, conflicting interests and intense local politics, a disconnect between global conservation discourses and local concerns, weak institutional arrangements, and global economic forces. The intense politics of access, control and use of natural resources challenge the implementation of a true polycentric regime in the Indian context due to a tendency to bureaucratization and a lack of participation, and existing limits to democratic citizenship. Creating a democratic space where multiple voices can be considered in the decision-making process remains a challenge. The paper concludes that inclusion of power and politics in the study of governance of natural resources should be of prime concern for researchers and decision makers.